Exploring the link: magnesium intake and hepatic steatosis in Americans - Chen, Xingxing; Fu, Liying; Zhu, Zhongxin; Wang, Yunchao (Frontiers in Nutrition, 2024)
The connection between magnesium and hepatic steatosis has not been well studied. This study aimed to explore the link between magnesium intake and hepatic steatosis, utilizing data from the National Health and Nutrition Examination Survey (NHANES) 2017-2020.The analysis included 5,935 participants, excluding individuals with hepatitis infection or substantial alcohol consumption. Magnesium intake assessment was based on 24-hour dietary recalls. Hepatic steatosis evaluation employed the controlled attenuation parameter (CAP), measured via transient elastography. Multivariate regression and subgroup analyses were conducted to scrutinize the relationship between magnesium intake and CAP values.Results: A higher magnesium intake was associated with lower CAP values, after adjusting for potential confounders. Subgroup analyses indicated an inverted Ushaped correlation between magnesium intake and CAP in women, White people, and non-hypertensive individuals, with respective inflection points at 126, 124.5, and 125 mg/day, respectively. Below these thresholds, a higher magnesium intake correlated with increased CAP values, while above these points, it was associated with decreased CAP.This extensive population-based study indicates an inverse relationship between magnesium intake and hepatic steatosis in Americans. This relationship displays an inverted U-curve, varying before and after specified inflection points in women, White people, and non-hypertensive individuals. These findings offer insights into tailored magnesium supplementation strategies for preventing and treating liver steatosis, based on gender and ethnicity.